2020
DOI: 10.3390/nu12092867
|View full text |Cite
|
Sign up to set email alerts
|

B Vitamins and One-Carbon Metabolism: Implications in Human Health and Disease

Abstract: Vitamins B9 (folate) and B12 are essential water-soluble vitamins that play a crucial role in the maintenance of one-carbon metabolism: a set of interconnected biochemical pathways driven by folate and methionine to generate methyl groups for use in DNA synthesis, amino acid homeostasis, antioxidant generation, and epigenetic regulation. Dietary deficiencies in B9 and B12, or genetic polymorphisms that influence the activity of enzymes involved in the folate or methionine cycles, are known to cause development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(162 citation statements)
references
References 208 publications
(242 reference statements)
3
155
1
3
Order By: Relevance
“…As this problem was described in an earlier work [33], one should ask another question: how will drinking these juices by the patient affect the cancer treatment during carboplatin therapy? Based on the literature, it can be said that high levels of some B vitamins can cause cancer or accelerate its development [34][35][36]. However, it is widely accepted that eating meals rich in vitamins and minerals, such as carrot and beetroot juice, reduces the likelihood of cancer, prevents it from metastasis, and may even help with cancer therapy.…”
Section: The Motivation Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As this problem was described in an earlier work [33], one should ask another question: how will drinking these juices by the patient affect the cancer treatment during carboplatin therapy? Based on the literature, it can be said that high levels of some B vitamins can cause cancer or accelerate its development [34][35][36]. However, it is widely accepted that eating meals rich in vitamins and minerals, such as carrot and beetroot juice, reduces the likelihood of cancer, prevents it from metastasis, and may even help with cancer therapy.…”
Section: The Motivation Of Workmentioning
confidence: 99%
“…Based on the literature, it can be said that high levels of some B vitamins can cause cancer or accelerate its development [ 34 , 35 , 36 ]. However, it is widely accepted that eating meals rich in vitamins and minerals, such as carrot and beetroot juice, reduces the likelihood of cancer, prevents it from metastasis, and may even help with cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…One-carbon metabolism is driven by the folate and requires B 6 as a cofactor. Folate and B 6 together regulate the DNA synthesis and methylation reactions ( 28 ). They play an important role in maintaining the stability of methylation patterns ( 28 ).…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…Extensive research has also demonstrated the importance of folate, vitamin 6, and vitamin B12 status in regulating OCM [ 20 , 42 , 43 , 44 , 45 , 46 ]. The classical symptom of folate and vitamin B12 deficiency is megaloblastic anemia caused by inhibition of DNA synthesis in erythropoietic cells in the bone marrow [ 46 ].…”
Section: Description Of the Transsulfuration Pathwaymentioning
confidence: 99%